(untitled) (Journal of Global Accounting, 2024)
The study examined the relationship between human resource (HR) practices and employee turnover among Nigerian commercial banks. Specifically, the study ascertained the degree to which staff career development policy, staff compensation policy and staff performance evaluation policy relates to employee turnover in the Nigerian commercial bank sector. Adopting a descriptive survey research design, the study was conducted using a population of 54,654 bank employees in Tier-1 commercial banks in Nigeria. The sample size was determined using Taro Yamane formula which showed an optimal sample of 397 respondents. Stratified sampling technique was utilised in the study. Primary data were collected via structured questionnaires. Descriptive analysis of the data employed frequency counts and percentages, while the hypotheses were tested using the Pearson correlation test. The findings revealed that: staff career development policy has a significant negative relationship with employee turnover in the Nigerian banking sector (r = -.551; p-value = 0.000); staff compensation policy has a significant negative relationship with employee turnover in the Nigerian banking sector (r = -.493; p-value = 0.000); staff performance evaluation policy has a significant negative relationship with employee turnover in the Nigerian banking sector (r = -.566; p-value = 0.000). In conclusion, effective human resource practices, including staff career development, compensation, and performance evaluation policies, are crucial in reducing employee turnover in commercial banks in Nigeria. The study recommends that the Management Board of commercial banks in Nigeria periodically review and adjust their compensation packages to remain competitive in the industry. This should include not only base salaries but also bonuses, benefits, and other financial incentives.